An Attempted Homicidal Cut Throat Injury: A Case Study - Sah, Mukesh Kumar; Thakur, Madhu (Journal of Karnali Academy of Health Sciences, 2020)
Homicidal cut throat is an injury over the front of neck by sharp instruments with an intent of murder. The neck contains vital structures (nerves, blood vessels, airway and pharyngeal conduit) in a compact fashion that may be difficult to access for physical examination or surgical exploration in a limited time. That is why these cases create panic and pose great challenges in the management. Here is a case of an attempted homicidal cut throat injury that highlights some of the challenges encountered in the management along with discussion on the evolving knowledge of the optimal management practice.